Kemampuan Interaksi Sosial Peserta Didik Tunanetra Kelas IV di SLB Nur Amalia Sumedang - Iskandar, Suci Rahmadiah; Suherman, Maman (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Students with visual impairments encounter significant challenges in developing social interaction abilities due to visual limitations that impact the learning process and adaptation to their surrounding environment. The background of this research is grounded in the importance of social interaction abilities for visually impaired individuals to actively participate in community life and reduce the risk of social isolation. This study aims to analyze the social interaction abilities of fourth-grade students with visual impairments, identify the difficulties they face, and describe the learning strategies implemented by teachers. The research methodology employed a qualitative approach with a descriptive design, involving two fourth-grade students with visual impairments and one classroom teacher as research subjects at SLB Nur Amalia Sumedang. Data collection was conducted through participatory observation, in-depth interviews, and documentation studies. Data analysis utilized techniques of data reduction, data presentation, and conclusion drawing. The research findings indicate that the social interaction abilities of students with visual impairments improved through the implementation of game-based cooperative learning methods and multisensory approaches. The primary difficulties identified include feelings of inferiority, social anxiety, limited social vocabulary, and lack of initiative to initiate interactions. Effective strategies encompass verbal communication training, role-playing activities, group discussions, and family collaboration. The research conclusion affirms that with appropriate approaches and comprehensive support, students with visual impairments can develop adequate social interaction abilities to actively participate in their social environment.